PENGARUH DISIPLIN KERJA, KEMAMPUAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN (Studi Kasus pada Bagian Operator Departemen Produksi PT UTAC Manufacturing Services Indonesia) - Kiasati Kania, (2021)
This research is using quantitative study aimed to know the influence of work discipline, work ability and work motivation on operator employee performance of production department PT UTAC Manufacturing Services Indonesia. The population is all operator employees of production departement PT UTAC Manufacturing Services Indonesia with a total of 189 employees. The number of samples used in this study was 65 operator employees using slovin sampling with the probability sampling method and the type of random sampling. Data collection is used through distributing questionnaires. The data analysis technique used is the Partial Least Square (PLS) method. The test result of this study are (1) work discipline has significant and positive effect on employee performance, (2) work ability has a significant and positive effect on employee performance, (3) and work motivation has a significant and positive effect on employee performance of operator on production departement PT UTAC Manufacturing Services Indonesia (4) work discipline, work ability, and work motivation simultaneously effect on employee performance of operator on production departement PT UTAC Manufacturing Services Indonesia.